Acute optic neuritis: Unmet clinical needs and model for new therapies. Issue 4 (August 2015) - Galetta, Steven L.; Villoslada, Pablo; Levin, Netta; Shindler, Kenneth; Ishikawa, Hiroshi; Parr, Edward; Cadavid, Diego; Balcer, Laura J.
Abstract : Idiopathic demyelinating optic neuritis (ON) most commonly presents as acute unilateral vision loss and eye pain and is frequently associated with multiple sclerosis. Although emphasis is often placed on the good recovery of high-contrast visual acuity, persistent deficits are frequently observed in other aspects of vision, including contrast sensitivity, visual field testing, color vision, motion perception, and vision-related quality of life. Persistent and profound structural and functional changes are often revealed by imaging and electrophysiologic techniques, including optical coherence tomography, visual-evoked potentials, and nonconventional MRI. These abnormalities can impair patients' abilities to perform daily activities (e.g., driving, working) so they have important implications for patients' quality of life. In this article, we review the sequelae from ON, including clinical, structural, and functional changes and their interrelationships. The unmet needs in each of these areas are considered and the progress made toward meeting those needs is examined. Finally, we provide an overview of past and present investigational approaches for disease modification in ON.